EVALUASI WEWENANG CAMAT DALAM MELAKUKAN PEMBINAAN DAN PENGAWASAN TERHADAP PEMERINTAHAN DESA (STUDI KASUS DI DESA PULAU BUSUK JAYA KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI TAHUN 2013) - Debi Monalisa; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Sub-district has been instrumental in giving encouragement or motivation to officials village to improve governance in the country, training in order to improve the ability of the apparatus of the village and make a comparative study out daerah. Role in the sub-district administrative guidance is to provide training and supervision in order to orderly administrasi. Coaching rule making and financial management of the village, sub-district only play a role in facilitating the development activities carried out in which the conduct training is part of the legal and financial parts of the district, sub-district party had never done coaching directly due to budget constraints in terms. Sub-district been instrumental in governance and development among rural districts where the district head region always involve village officials, BPD, LPM and community leaders in the district. Implementation activities undertaken Kabupaten Kuantan Singingi Kecamatan Inuman in improving the performance of the apparatus villages had barriers namely the lack of human resources and less budget village officials in the implementation of development, but the sub-district also received support in improving the performance of village officials that the presence of a high spirit of village officials in following development activities are carried out and also the support of the village to the party apparatus subdistrict to always conduct development activities in order to improve the performance of the governance of Desa Pulau Busuk Jaya.Keywords: Evaluation Authority District Head, Development, Supervision, Government.UIL